Indicator species characterization and removal in a detention pond in the Plaster Creek watershed. (15th November 2021) - Vander Meer, Luke; DeHeer, Katherine; Mellinger, Joseph; Gibes, Sarah; Paasch, Bradley; Wildschut, Julie; Miller, William L.; He, Sheng-Yang; DuBois, Kelly N.
Abstract: Microbial pathogen contamination is a leading cause of impairment for urban rivers and streams in Michigan. Reports on the ability of green infrastructure best management practices to remove microbial pathogens have been highly variable. This study evaluated the influence of a detention basin (Kreiser Pond) on microbial dynamics in the Plaster Creek watershed in West Michigan. High levels of fecal indicator bacteria and coliphage were documented in influent and effluent water, with significant increases in indicator microbe concentrations during storm events. In dry conditions, Kreiser Pond efficiently reduced the number of indicator microbes flowing through the basin. Rainfall volume had a greater influence on the diversity of bacteria than sampling location. Antibiotic resistance was prevalent in culturable E. coli from Kreiser Pond, demonstrating a potential public health risk and highlighting the need for identifying the ultimate sources of microbial pollution. Highlights: High levels of indicator microbes in Kreiser Pond increase significantly during storm events. In dry conditions Kreiser detention pond reduces indicator microbes flowing downstream. Sampling conditions affect the microbial composition and diversity of samples. Residential runoff entering Kreiser Pond contains antibiotic resistant E. coli .